DYNAMIC CHARACTERISTICS OF MOTOR AND COGNITIVE FUNCTIONS AMONG STUDENTS ENGAGED IN GYMNASTICS - Budyka , E.V.; Enikolopova, E.V.; Volodina, E.S.; Komarov А.М. (Modern Psychology, 2021)
The present work is devoted to the analysis of the speed and regulatory characteristics of motor and cognitive functions in students of different genders and levels of sports qualification engaged in gymnastics. The study involved students of various faculties of the Lomonosov Moscow State University - 40 boys and 26 girls, whose lateral profile of motor and sensory functions was previously determined. Tapping test and Hand-Dominanz-Test (HDT) were used to study the dynamic components of motor functions. The dynamic characteristics of cognitive processes were evaluated using the Color-Word Interference Test - a modification of the Stroop test from the D-KEFS battery and the Compass test. It was found that the speed indicators of both motor and cognitive functions were higher in young men, regardless of the level of sports qualification. Voluntary regulation of motor functions is more effective among female students than among students. The results of the study indicate that such an indicator of the voluntary regulation of cognitive processes as cognitive flexibility is higher in young men compared to girls and in more highly qualified athletes, regardless of gender. The connection of individual characteristics of motor and cognitive processes with success in the chosen sport is discussed.